2022
DOI: 10.26434/chemrxiv-2022-k7gs1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phytochemicals based therapeutic approaches for Breast cancer targeting: Molecular docking study

Abstract: Background: Cancer is a prominent cause of disease burden all over the world. Primary cause of the development of cancer is exposure to potentially hazardous environmental factors and unhealthy lifestyle. Among all types of cancer, breast cancer is most common in women and becomes a public health issue on a global scale. There has been considerable interest in the development of drugs which can target cancer-causing hotspot factors such as mTOR, estrogen receptor alpha, and progesterone receptor to cure breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 85 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…As they are genetically unique to each patient, tissue organoid has provided alternative ways of preclinical drug testing and are now being used for the development of “personalized medicine” for several diseases. Organoids have been effectively generated and their application has been demonstrated in various fields, including drug screening, disease modeling, tissue transplant, pathogenesis, and regenerative medicine (Ashok et al, 2020; Parihar, Ferdous Sonia, et al, 2022; Parihar, Puranik, et al, 2022; Parihar, Sonia, et al, 2022; Parihar, Zafar, et al, 2022). In vitro models are more reproducible, permitting a larger sample size to be evaluated on multiple models in a smaller duration of time.…”
Section: Introductionmentioning
confidence: 99%
“…As they are genetically unique to each patient, tissue organoid has provided alternative ways of preclinical drug testing and are now being used for the development of “personalized medicine” for several diseases. Organoids have been effectively generated and their application has been demonstrated in various fields, including drug screening, disease modeling, tissue transplant, pathogenesis, and regenerative medicine (Ashok et al, 2020; Parihar, Ferdous Sonia, et al, 2022; Parihar, Puranik, et al, 2022; Parihar, Sonia, et al, 2022; Parihar, Zafar, et al, 2022). In vitro models are more reproducible, permitting a larger sample size to be evaluated on multiple models in a smaller duration of time.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one of the alternative broad therapeutic spectra against COVID-19 virus infection is the search for plant-based natural enzyme inhibitors using virtual screening, to obtain drugs with minimal side effects [27][28][29][30][31] . The flavonoids and non-flavonoid phenolic, terpenes, and alkaloids are explored as promising therapeutic class having potential antiviral activities due to their inherent properties such as antioxidant, immunomodulatory, and anti-inflammatory roles that could reduce the severity of infection, disease symptoms and enhance the immune response of the patient [32][33][34] . Recent studies reported the antiviral activity of plant-based phytochemicals to bind with SARS-CoV-2 spike protein and ACE2 receptor 35 .…”
Section: Introductionmentioning
confidence: 99%